Model Pentahelix Dalam Pengembangan Pariwisata Berkelanjutan Di Kabupaten Pekalongan Jawa Tengah - Harimurti, Harimurti; Sunarjo, Wenti Ayu (LPPM Universitas Pekalongan, 2024)
Developments in tourism development experience dynamics and rapid adaptation. Tourism activity is a good development catalyst. Tourism activity increased economic growth increased. This economic growth can have an impact on the level of population welfare and is expected to be able to reduce economic problems such as: unemployment and poverty. Tourism has a positive trend in terms of quantity in Indonesia. Phenomena like this should be responded positively by the government by making improvements and enhancing the quality and quality of tourism activities in Indonesia. So far, tourism activities have not been fully supported by quality road access to tourist attractions and the lack of nature conservation efforts. Sustainable tourism reduces the negative impacts of tourism activities on the environment, society and the economy to achieve an ecological balance that is sustainable, economically viable, and ethically and socially just. The Pentahelix tourism development model is expected to be able to realize sustainable tourism. The Pentahelix style of the five elements is referred to as a determinant of tourism success.